WEO and WCO as a Rejuvenating Agent in Aged Bitumen - Sunny, Tina Maria; Pynadath, Agin Rose; Mohanan, Aiswarya; K, Ajith; E K, Akheel (International Journal of Scientific Research in Civil Engineering, 2018)
Bitumen is a useful and expensive material with high thermal sensitivity. Despite the limited resources, it has been applied in abundance (110 million tonnes annually in the world) in the high-way industry. Bitumen is a useful and expensive material with high thermal sensitivity .The ageing of the bitumen during storage, mixing, transport and laying on the road, as well as in service life, are the most important problems presented by the use of bitumen in pavements. This paper investigates the possibility of using Waste Cooking Oil (WCO) and Waste Engine Oil (WEO) which is a waste material that pollutes landfills and rivers, as an alternative natural rejuvenating agent for aged bitumen to a condition that resembles the original bitumen. With this target, the physical and chemical properties of the original bitumen, aged bitumen and rejuvenated bitumen were measured and compared by the bitumen binder tests – softening point, penetration, ductility, viscosity and specific gravity. In addition, the behaviour of the WCO and WEO rejuvenated bitumen is investigated and compared with virgin bitumen. The aged bitumen is rejuvenated by 2%, 3%,4% and 5% of waste cooking oil and waste engine oil by the total weight of bitumen.
Keywords: Aged bitumen; Rejuvenating agent; Waste cooking oil; Waste engine oil; Reclaimed Asphalt Pavement